Clinical value of coagulation parameters in predicting the severity of severe fever with thrombocytopenia syndrome - Xia, Yanyan; Jia, Bei; Chen, Yuxin; Wang, Sen; Xu, Xuejing (Frontiers in Microbiology, 2024)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease caused by a novel bunyavirus infection with a high lethality rate. The purpose of this study was to investigate the changes in coagulation parameters in patients with SFTS, aiming to provide clinical evidence for early diagnosis, treatment, and disease analysis. A total of 40 patients with SFTS attended from April 1, 2020 to May 21, 2022 in Nanjing Drum Tower Hospital were selected and grouped according to the duration of the disease, mild and severe disease, cure and death, with 50 healthy physical examiners as controls, and the risk of severe and death disease was predicted using ROC curves. Comparison between the healthy, mild and severe groups revealed that PT, INR, APTT, TT, D-D and vWF levels were higher than those in the healthy control group, and FⅡ, FⅨ, FⅩ, FⅪ, FⅫ, PC and PS levels were lower than those in the healthy control group, the differences were statistically significant (P<0.05).Comparing the results of SFTS patients with different course times, the results of Fib, FⅤ, FⅦ, FⅧ, FⅨ, FⅩ, FⅪ were statistically significant (P<0.05). Among the survived and deceased patients, the PT, INR, DD and PS results of the deceased patients were higher than those of the survived patients, and the FⅧ, FⅨ, FⅪ, FⅫ and PC were lower than those of the survived patients. The area under the ROC curve showed that D-D had higher predictive ability for the risk of severe disease (AUROC 0.93, sensitivity and specificity at a Cut-off value of 1.50 mg/L were 90.0% and 86.5%, respectively) and the risk of death occurring (AUROC 0.84, sensitivity and specificity at a Cut-off value of 3.39 mg/L were 87.5% and 80.0%, respectively). The monitoring of the coagulation parameters in patients with SFTS is great significance for identifying the severity and death of the patient's condition, and it is of great clinical value to provide early attention, timely intervention and maximum reduction of the mortality rate for patients at risk of severe disease.